A harmonized database to follow the demographic trajectories of European cities, the TRADEVE database (Demographic Trajectories of European Cities) - Marianne Guérois (Unité Mixte de Recherche 8504 Géographie-cités, 2019)
TRADEVE Database provides the following information for the European Urban Morphological Zones (UMZ) of more than 10 000 inhabitants in 2011:- Name of UMZ- Name of country- Code corresponding to the vectorial maps- Population for 1961, 1971, 1981, 1991, 2001, 2011- Accompanied by vectorial maps of the UMZ perimeters for 1961, 1971, 1981, 1991 and 2001.TRADEVE database is based on Urban Morphological Zones (UMZ) (EEA, 2004). UMZ were enriched in the ESPON Database Project 2008-2014 by giving a name to UMZ and by creating a correspondence dictionary between UMZ and Local Administrative Units (LAU). A population density grid from the Joint Research Centre was originally used for attributing populations to UMZ. The integration of time comes from a retropolation of UMZ 2000 back to 1961.The Historical Population Database of European LAUs allowed to attribute population for six dates (from 1961 to 2011), in the geometry of the 2012 LAU. A data model provided evolving urban perimeters from the retropolation of UMZ 2000 back to 1961. Two criteria were used: contiguity and minimal population (2000 inhabitants) of the building blocks. The population change between 2001 and 2011 has been registered within the limits of UMZ 2000.